Migration and Net FDI: Role of Governance - Aldabbas, Hazem; Lahrech, Abdelmounaim; Juusola, Katariina (Migration Letters, 2023)
Although the relationship between migration and Foreign Direct Investment (FDI) has been extensively explored in the literature. A notable gap exists in understanding the role of governance in shaping this relationship. This research has primarily focused on the direct links between migrants and FDI, dominating the importance influence of governance structures. Therefore, the aim of this study is to investigate the role of governance as a critical moderator influencing the migration-FDI relationship. We substantiate our conceptual model by applying it to an extensive global panel dataset covering 48 countries spanning from 2011 to 2019. Using Process Macro to test our hypotheses. The results reveal that a robust governance structure in a specific country enhances the relationship between migration and FDI directed towards that nation. The result revealed that 78% of net FDI comes from migrants and structure governance of hosted countries. Particularly, positive relationship between migration and FDI was significantly stronger at a higher level of governance. Therefore, our study introduces new insights into the boundary conditions that influence and provide an answer for when migration shapes the dynamics of FDI net flows through moderating role of governance.